2021
DOI: 10.4067/s0717-95022021000401081
|View full text |Cite
|
Sign up to set email alerts
|

Professional Esports Players are not Obese: Analysis of Body Composition Based on Years of Experience

Abstract: Esports are considered a form of electronic sports that have become an important element of popular culture. Its evolution and continuous development have led to consider esports as a profession, increasing the number of players, practice modalities and hours of play dedicated to this field. Therefore, scientific and economic contributions have increased in recent years, however, there is little research on body composition in this group of players. To describe the anthropometric characteristics and body compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…In relation to BMI, 49.6% of the sample that participated in this research is normal weight, which is in line with the results recorded by Giakoni et al [ 31 ], who conducted a study with a sample of Spanish professional esports players, allowing to determine a clear trend regarding the body composition of the subjects, stating that players have mostly a normal weight, ruling out the prevalence of overweight and/or obesity. On the other hand, the results found by Trotter et al [ 32 ] indicated that the BMI of esports players from Germany, Canada, and the United Kingdom differed significantly from the global BMI reference data of the general population, with esports players being more likely to have their BMI classified as normal weight and pre-obese; in addition, a healthier BMI was associated with higher physical activity level and higher levels of perceived general health [ 32 ]; these results coincide with the results of the study by Trotter et al [ 32 ] and Paramitha et al [ 49 ], who in the analysis of a sample of 50 professional gamers, found a BMI = 22.4, which is considered normal weight.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In relation to BMI, 49.6% of the sample that participated in this research is normal weight, which is in line with the results recorded by Giakoni et al [ 31 ], who conducted a study with a sample of Spanish professional esports players, allowing to determine a clear trend regarding the body composition of the subjects, stating that players have mostly a normal weight, ruling out the prevalence of overweight and/or obesity. On the other hand, the results found by Trotter et al [ 32 ] indicated that the BMI of esports players from Germany, Canada, and the United Kingdom differed significantly from the global BMI reference data of the general population, with esports players being more likely to have their BMI classified as normal weight and pre-obese; in addition, a healthier BMI was associated with higher physical activity level and higher levels of perceived general health [ 32 ]; these results coincide with the results of the study by Trotter et al [ 32 ] and Paramitha et al [ 49 ], who in the analysis of a sample of 50 professional gamers, found a BMI = 22.4, which is considered normal weight.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the participants in the sample had to indicate their body weight (kg) and height (cm) on the form. With these data, the body mass index (BMI = kg/m 2 ) was obtained, which made it possible to determine the nutritional status according to the categories, including undernutrition, normal weight, overweight, and obesity, based on the guidelines of the WHO [ 27 ] according to gender and average age and used in a previous study on body composition of professional esports players by Giakoni-Ramírez, Duclos-Bastías, and Yañez-Sepúlveda [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Big data technology is not a completely new concept for most experts and academics. When data is stored to a certain extent and traditional methods are no longer effective [16], it is an unavoidable result of technological progress. AI and machine learning are frequently associated with big data.…”
Section: Big Data Technology and Cbamentioning
confidence: 99%
“…Thus, they could allow researchers to describe the influence that esports can have on PA, as well as explain and understand the underlying reasons players engage in, continue, resume, or abandon PA. Based on these different approaches, different quantitative and qualitative methodologies appear to be complementary. Following the example of Schary et al (2022), we encourage the implementation of longitudinal cohort studies, such as the recent study by Giakoni-Ramírez et al (2021), which undertakes a one-year follow-up with 53 professional esports players to observe the influence of esports on body composition. Finally, semi-structured interviews appear to be essential for understanding the influence of esports on PA.…”
Section: Influence Of Esports On Physical Activitymentioning
confidence: 99%